Accounting Risk Causes and Countermeasures of Commercial Banks - Xiao, Weiguo (Journal of Theory and Practice of Management Science, 2023)
This paper mainly focuses on accounting risks in commercial banks. With accounting risks as the entry point and ft targeted solutions, we hope that through the main discussion, we can promote the stable operation of Chinese commercial banks and make ft contribution to our economy.